HERP, a Novel Heterodimer Partner of HES/E(spl) in Notch Signaling - Iso, Tatsuya (American Society for Microbiology, 2001)
HERP1 and -2 are members of a new basic helix-loop-helix (bHLH) protein family closely related to HES/E(spl), the only previously known Notch effector. Like that of HES, HERP mRNA expression is directly up-regulated by Notch ligand binding without de novo protein synthesis. HES and HERP are individually expressed in certain cells, but they are also coexpressed within single cells after Notch stimulation. Here, we show that HERP has intrinsic transcriptional repression activity. Transcriptional repression by HES/E(spl) entails the recruitment of the corepressor TLE/Groucho via a conserved WRPW motif, whereas unexpectedly the corresponding—but modified—tetrapeptide motif in HERP confers marginal repression. Rather, HERP uses its bHLH domain to recruit the mSin3 complex containing histone deacetylase HDAC1 and an additional corepressor, N-CoR, to mediate repression. HES and HERP homodimers bind similar DNA sequences, but with distinct sequence preferences, and they repress transcription from specific DNA binding sites. Importantly, HES and HERP associate with each other in solution and form a stable HES-HERP heterodimer upon DNA binding. HES-HERP heterodimers have both a greater DNA binding activity and a stronger repression activity than do the respective homodimers. Thus, Notch signaling relies on cooperation between HES and HERP, two transcriptional repressors with distinctive repression mechanisms which, either as homo- or as heterodimers, regulate target gene expression.